Seismostratigraphy of the Siberian Sector of the Arctic Ocean and adjacent Laptev Sea Shelf - Weigelt, Estella; Jokat, Wilfried; Franke, Dieter (Journal of Geophysical Research: Solid Earth, 2014)
A new seismostratigraphic model has been established within the Arctic Ocean adjacent to the East Siberian Shelf on the basis of multichannel seismic reflection data acquired along a transect at 81°N. Ages for the sedimentary units were estimated via links to seismic lines and drill site data of the US Chukchi Shelf, the Lomonosov Ridge, and the adjacent Laptev Shelf. Two distinct seismic units were mapped throughout the area and are the constraints for dating the remaining strata. The lower marker unit, a pronounced high-amplitude reflector sequence (HARS), is the most striking stratigraphic feature over large parts of the Arctic Ocean. It indicates a strong and widespread change in deposition conditions. Probably, it developed during Oligocene times when a reorientation of Arctic Plates took place, accompanied by the gradual opening of the Fram Strait, and a widespread regression of sea level. The top of the HARS likely marks the end of Oligocene/early Miocene (23Ma). An age estimate for the base of the sequence is less clear but likely corresponds to base of Eocene (˜56Ma). The second marked unit detected on the seismic lines parallels the seafloor with a thickness of about 200ms two-way travel time (160 m). Its base is marked by a change from a partly transparent sequence with weak amplitude reflections below to a set of continuous high-amplitude reflectors above. This interface likely marks the transition to large-scale glaciation of the northern hemisphere and therefore is ascribed to the top Miocene (5.3 Ma).